Prosedur pengembangan media audio visual untuk pembelajaran pencak silat dasar - Mukholid, Agus; Kustiawan, Andri Arif; Alexander, Bimo (Jurnal Porkes, 2023)
The results of a survey in the field at the Penjaskesrek Study Program and the Penkepor Study Program of FKIP UNS Surakarta and the Penkepor Study Program of FKIP Tunas Pembangunan University (UTP) Surakarta, showed that lecturers of pencak silat theory and practice (TP) courses still lack learning media. The goal is to produce audio-visual media for basic pencak silat learning in sports colleges. This research is a development research or called the term R & D (Research and Development), which aims to develop audio-visual learning media on basic martial arts learning in sports colleges. Needs analysis research is used to produce learning media products that are in accordance with the needs. The results showed that with the application, students became more interested in learning martial arts and their attitude towards multimedia systems was very open and accepting. In addition, it was also found that students' mastery of martial arts material became better so that it can be concluded that this application is very useful in helping students have good knowledge, skills, and attitudes towards martial arts.